2007
DOI: 10.1097/acm.0b013e3181574a62
|View full text |Cite
|
Sign up to set email alerts
|

From Traditional to Patient-Centered Learning: Curriculum Change as an Intervention for Changing Institutional Culture and Promoting Professionalism in Undergraduate Medical Education

Abstract: The authors reframe a curriculum change from a traditional lecture-based to an integrated patient-centered approach as an intervention for changing the culture and hidden curriculum of an institution in ways that promote professionalism. Within this context, the authors articulate some of the inherent process and relational factors brought about by these curricular changes that are essential elements of this intervention process. In 1998 the University of North Dakota School of Medicine and Health Sciences (UN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
53
0
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(62 citation statements)
references
References 28 publications
0
53
0
3
Order By: Relevance
“…In a similar vein, Christianson et al advocate a patientcentred curriculum in early years of training as a way to bring about organisational cultural shift towards an outward rather than inward focus, countering the hidden curriculum and enhancing development of professionalism (Christianson et al 2007). …”
Section: Role Modellingmentioning
confidence: 99%
“…In a similar vein, Christianson et al advocate a patientcentred curriculum in early years of training as a way to bring about organisational cultural shift towards an outward rather than inward focus, countering the hidden curriculum and enhancing development of professionalism (Christianson et al 2007). …”
Section: Role Modellingmentioning
confidence: 99%
“…We hypothesize this was because pre-clinical education was not perceived as belonging to any one Department in particular, and because all Departments were required to contribute equally to the tutor training. During the process of change, we appear to have been successful in communicating and building relationships with the faculty, and in providing them with the skills needed for them to change the way they teach; these factors have been identified as being of critical importance and are demonstrated by the high rates of workshop participation, course participation and retention of tutors (Rollins et al 1999;Christianson et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…9 Various formats for teaching ethics and professionalism to health care students have been described, including small-group case discussion, peer-review, role-play, and self-reflection. [10][11][12][13] While ethical concepts can be communicated via lecture-style presentations, exposure to ethically-challenging situations allows students to visualize and reflect how actions affect others and society as a whole. Rosenstein and colleagues found that psychiatric fellows, following the completion of a course on ethics, showed a desire for a more interactive format.…”
Section: Discussionmentioning
confidence: 99%